2021
DOI: 10.1016/j.heliyon.2021.e08608
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing of geothermal energy for a greenhouse in Ecuador employing a heat pump: design, construction, and feasibility assessment

Abstract: Globally, the greenhouses' farming area comprises 500 000 ha, and they efficiently produce more than half of the vegetables consumed around the world. Nevertheless, high-yield crops tend to be incredibly energy-intensive. This study proposes designing and building a coupled geothermal heat pump for a 470 m 2 greenhouse in the Andean zone conditions addressing a requirement of 15 °C at night and 30 °C during the day. Firstly, the study determined the energy potential of the solar and geot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(32 reference statements)
1
11
0
Order By: Relevance
“…The study concluded that the heat pump system can provide energy efficiency of 25% to 65% more than traditional combustion-based systems [148]. Technical assessment is provided to harness geothermal energy for heating/cooling systems of greenhouse farming in Ecuador [149].…”
Section: Agricultural Demand Flexibilitymentioning
confidence: 99%
“…The study concluded that the heat pump system can provide energy efficiency of 25% to 65% more than traditional combustion-based systems [148]. Technical assessment is provided to harness geothermal energy for heating/cooling systems of greenhouse farming in Ecuador [149].…”
Section: Agricultural Demand Flexibilitymentioning
confidence: 99%
“…It should be noted that this work needs to determine the number of boreholes in combination with the load of the proposed building in the region. If the number of boreholes is insufficient, geothermal boreholes can be supplemented at an appropriate position, but it should be noted that the distance between the boreholes cannot be less than 5 m, otherwise it will cause cold and hot accumulation effect [51][52].…”
Section: Based On Vertical Drilling Technologymentioning
confidence: 99%
“…The authors investigate the distribution of losses in the system over the elements of the system separately, and the equivalent CO 2 emissions of heating a greenhouse with natural gas and an HP system was compared. Chiriboga et al confirmed the possibility of designing and building a coupled geothermal HP [13]. Based on the results of the assessment of the energy potential of the solar and geothermal sources, the energy balance in the greenhouse was calculated to determine the parameters of the geothermal HP using the vapor compression cycle.…”
Section: Introductionmentioning
confidence: 99%